Border/Lines : Canada's magazine of cultural studies. (Toronto : Border/Lines Magazine Society.)
Fonds Suzan Daniel (FSD)
Periodiciteit: driemaandelijks
Redactie: 183 Bathurst Street, Toronto, Ontario M5T 2R7
Engels
Periodiek